Digital Transformation in School Administration: Enhancing Correspondence and Archival Systems - M. Yasman Rahma Jaya; Riyuzen Praja Tuala; Devin Cumbuan Putri; Yosep Aspat Alamsyah (Journal of Educational Management Research, 2026)
This study aims to analyze the management of administrative services in correspondence and records management and the role of information technology in supporting administrative effectiveness using a descriptive qualitative approach, with data collected through interviews, observations, and documentation and analyzed using the Miles and Huberman model; the findings indicate that correspondence and records management have been implemented systematically through processes of document receipt, recording, numbering, disposition, distribution, storage, security, classification, maintenance, retrieval, and retention, supported by a digital service system that enhances effectiveness, efficiency, accuracy, and security, although challenges such as increasing document volumes, limited storage capacity, and incomplete digitization remain; therefore, the study implies that strengthening digital administrative systems and accelerating records digitization are essential for improving the quality, accessibility, sustainability, and efficiency of administrative services.